2021
DOI: 10.1155/2021/5838510
|View full text |Cite
|
Sign up to set email alerts
|

Early Sexual Debut among Ghanaian Women: Correlates and Psychological Effect

Abstract: Early sexual initiation is linked to an increased risk of HIV/AIDS and other STIs among teenagers, as well as having multiple partners, not using contraception, unintended pregnancy, and illegal abortions. Aim. To identify the correlates and psychological effects of early sexual debut among not-in-union women in Ghana. A descriptive cross-sectional survey was used for this study using data from Ghana Multiple Indicator Cluster Survey (MICS) for the year 2017/2018. SPSS software was used for data analysis, biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
(41 reference statements)
3
14
5
Order By: Relevance
“…The odds of early sexual initiation were less likely among female aged 20-24 years than among female aged 15-19 years, which consistent with study in Africa [12,[36][37][38]. This could be due to cultural behaviors such as early marriage and abduction, which were popular at the time.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The odds of early sexual initiation were less likely among female aged 20-24 years than among female aged 15-19 years, which consistent with study in Africa [12,[36][37][38]. This could be due to cultural behaviors such as early marriage and abduction, which were popular at the time.…”
Section: Discussionsupporting
confidence: 85%
“…Youth who started their first cohabitation at the ages of less than 15 years and 15-19 years were more likely to have early sexual initiation than those who started cohabitation at the ages of 20-24 years, respectively this finding was supported by study in Ghana [38].This study found that youth females who used contraception had a higher risk of early sexual debut than their counterparts, which is consistent with other studies in Africa [2]. This could be because young people who take contraception are less likely to become pregnant and have more confidence to begin sexual activity at a young age.…”
Section: Discussionmentioning
confidence: 56%
“…Most participants engaged in sexual activities during their adolescent period, and it was high among persons within the age groups of 16-20 years. Other recent studies in the northern region of Ghana reported sexual activities among 16 years and above [25][26][27][28][29][30]. Important in this study is the finding of early use of contraceptives among our study participants, re-emphasising a need to target teenagers in family planning services in Ghana.…”
Section: Discussionmentioning
confidence: 61%
“…It is a cross-sectional study conducted every five-year to generate updated health and health-related information. The information was gathered in partnership with the International Classification of Functioning, Disability, and Health (ICF) and Measure DHS in each country [ 4 ]. The research was based on the most recent standard Demographic and Health Survey (DHS) of 33 sub-Saharan African countries conducted from 2011–2021.…”
Section: Methodsmentioning
confidence: 99%
“…Early sexual initiation is defined as an experience of first intercourse before 15 years of age [ 1 , 2 ]. Early sexual activity, particularly in developing nations, has been reported to cause social and public health issues [ 3 , 4 ]. Early sexual practice at a young age is a global public health issue that is particularly prevalent in low-and middle-income countries such as sub-Saharan African countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%